2009
DOI: 10.1002/tax.581017
|View full text |Cite
|
Sign up to set email alerts
|

Male and female separation event trapped in a species tree

Abstract: The species-rich genus Carex (Cyperaceae) is one of the 7% of angiosperm genera containing dioecious species. Dioecy is rare in Carex, only 12 spp. out of the 1,776 recorded taxa having been identified as dioecious. This paper focuses on Carex davalliana and C. dioica, the two dioecious species recorded in Europe. We investigated the nuclear (ITS) and chloroplast (trnTLF, rpl16) phylogenies of European Carex and identified incongruence in the phylogenetic history of both C. davalliana and C. dioica. This incon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Dioecy appears in both clades. Dioecy is advantageous in an environment with changing conditions (Bertin 2007), but is quite rare in Carex, occurring in only 0.68% of species (Guibert et al 2009). The derived positions of the dioecious species Carex scirpoidea Michx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dioecy appears in both clades. Dioecy is advantageous in an environment with changing conditions (Bertin 2007), but is quite rare in Carex, occurring in only 0.68% of species (Guibert et al 2009). The derived positions of the dioecious species Carex scirpoidea Michx.…”
Section: Discussionmentioning
confidence: 99%
“…Timonen (1998) also considered dioecious species the most specialized. Guibert et al (2009) suggested that hybridization between monoecious species with conflicting sexual morphology (gynecandrous and androgynous) could induce dioecy. The inflorescence of the dioecious species is similar to the androgynous unispicate Carex of the Caricoid Clade.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence that inbreeding depression occurs and is selected against is strong (Schemske and Lande, 1985; Ashman, 2006). However, many outcrossing mechanisms less extreme than dioecy exist (e.g., self‐incompatibility, dichogamy, when a flower matures the different sexual functions at different times, and herkogamy, when the male and female sexual structures are spatially separated) and occur in species that are ancestral to dioecious species (Ornduff, 1966; Freeman et al, 1997; Guibert et al, 2009), thus calling into question the primacy of selfing as the driving force behind the evolution of dioecy. Similarly, specialization in the form of flower location within the plant exists in some monoecious species such as Sagittaria trifolia (Huang et al, 2002), in which flowers at the base of the raceme are female and flowers at the tip of the raceme are male.…”
Section: Methodsmentioning
confidence: 99%
“…The range of mixed sexual systems (e.g. androdioecy, andromonoecy, gynodioecy, gynomonoecy) probably evolved via a spatial separation of unisexual flowers occurring in monoecious or dioecious plants (Barrett, ; Guibert et al., ). Renner () suggests that the relatively few reports of, for example, gynodioecy (populations with bisexual/hermaphroditic individuals and female individuals) and other mixed sexual systems, compared to monoecy, may be an artefact of scarce fieldwork on tropical plants.…”
Section: Introductionmentioning
confidence: 99%